2012
DOI: 10.1136/bcr.01.2012.5635
|View full text |Cite
|
Sign up to set email alerts
|

An occult filarial infection presenting as chyluria with proteinuria: a case report and review of literature

Abstract: Chyluria is the passage of chyle into urine, and develops as a result of communication between the lymphatic system and the urinary system. It is an unusual manifestation of lymphatic filariasis reported mainly from South Asian countries. We report the case of a 38-year-old man from an endemic area who presented with passage of milky urine. Physical examination did not reveal any lymphadenopathy or lymph oedema. Urine tests revealed nephrotic range proteinuria. A 99m technetium sulphur colloid lymphoscintigrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Sometimes chyluria can be mistaken for proteinuria of nephrotic syndrome . Hypocholesterolemia is a characteristic feature of chyluria, and helps to differentiate it from proteinuria of nephrotic syndrome, where hypercholesterolemia is a feature .…”
Section: Clinical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes chyluria can be mistaken for proteinuria of nephrotic syndrome . Hypocholesterolemia is a characteristic feature of chyluria, and helps to differentiate it from proteinuria of nephrotic syndrome, where hypercholesterolemia is a feature .…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Sometimes chyluria can be mistaken for proteinuria of nephrotic syndrome. 10,24,25 Hypocholesterolemia is a characteristic feature of chyluria, and helps to differentiate it from proteinuria of nephrotic syndrome, where hypercholesterolemia is a feature. 26 This differentiation is critical to avoid unnecessary renal biopsy in patients with heavy proteinuria as a result of chyluria rather than nephrotic syndrome.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Saha et al diagnosed chyluria by lymphoscintigraphy and found their patient to be positive for filariasis. They treated the patient with diethylcarbamazine initially; however, surgical closure was needed, as the patient did not respond to medical therapy [ 13 ]. Sivashankar et al reported a case of chyluria that was managed by endoscopic sclerotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%